Kyrgyz Republic : Fourth and Fifth Reviews under the Three-Year Arrangements under the Extended Credit Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Kyrgyz Republic's Fourth and Fifth Reviews Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria (PCs). Program performance has been mixed. All end-December 2016 and end-June 2017 quantitative PCs, and all but three indicative targets (ITs) were met. The December 2016 IT on tax revenue, the continuous IT on introducing new or renewing existing tax exemptions, and the June 2017 IT on reserve money were not observed. Six structural benchmarks were missed, of which five were proposed to be postponed or modified at the time of the fourth review. Resuming the reform agenda and pursuing consolidation efforts are essential to allow growth to reach its potential over the medium term.